2002
DOI: 10.1038/sj.bjp.0704443
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of the novel mammalian tachykinin, hemokinin 1

Abstract: 1 The e ects of the novel mammalian tachykinin, hemokinin 1 (HEK-1), have been investigated by radioligand binding and functional in vitro and in vivo experiments. 2 Similar to SP (K i =0.13 nM), HEK-1 inhibited in a concentration-dependent manner and with high a nity [ 3 H]-substance P (SP) binding to human NK 1 receptor (K i =0.175 nM) while its a nity for [ 125 I]-neurokinin A (NKA) binding at human NK 2 receptor was markedly lower (K i =560 nM). 3 In isolated bioassays HEK-1 was a full agonist at tachykini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 31 publications
(45 reference statements)
5
59
0
1
Order By: Relevance
“…Diversity in the amino acid sequence between these naturally occurring NK 1 ligands appears moderately flexible, and this is especially significant with regard to their role and functions. In bioassays, mHK-1 produces hypotension in guinea pigs and salivary secretion in rats in the same way as SP (12). In rats, we have shown that the complex, but characteristic, regional hemodynamic response to SP (26) is closely mimicked by EKA͞B.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Diversity in the amino acid sequence between these naturally occurring NK 1 ligands appears moderately flexible, and this is especially significant with regard to their role and functions. In bioassays, mHK-1 produces hypotension in guinea pigs and salivary secretion in rats in the same way as SP (12). In rats, we have shown that the complex, but characteristic, regional hemodynamic response to SP (26) is closely mimicked by EKA͞B.…”
Section: Discussionmentioning
confidence: 72%
“…In mice and humans, the TAC4 gene is widely distributed with expression levels and sites distinct from that of the TAC1 gene, particularly within the peripheral tissues. The peripheral expression of TAC4 is therefore particularly intriguing because mHK-1 has been shown to be a full agonist at each of the three NK receptors, with a remarkable selectivity for the NK 1 receptor that is similar to that of SP (11,12). This leads us to propose that mHK-1 and EKA͞B are the peripheral SP-like endocrine͞paracrine agonists where SP is not expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its primary ligand is SP, but other members of the tachykinin family can also activate NK-1R, including hemokinin-1 at equimolar affinity to SP (29,30), and neurokinins A and B at lower affinity (31). There are several potential sources of SP that could activate tr-NK-1R in CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, it most closely resembles SP in that both have multiple cationic residues at the N terminus and an aromatic amino acid occupying the variable X position of the tachykinin motif. Moreover, HK-1 demonstrates similar binding affinity and preference for the SP receptor, NK-1 (21)(22)(23)(24)(25)(26). However, there are remarkable differences in tissue distribution between HK-1 and SP.…”
mentioning
confidence: 97%